"EFFECT OF HIGH VERSUS LOW DOSES OF HUMAN RECOMBINANT ERYTHROPOIETIN ON THE ANEMIA OF PREMATURITY" - A. Mohammadzadeh; F. Naseri (Acta Medica Iranica, 2005)
Recombinant human erythropoietin (rh-EPO) is known to accelerate erythropoiesis in preterm infants. The purpose of this study was to compare the effectiveness of early treatment with two doses of rh-EPO (high vs. low dose) in the management of anemia of prematurity. Twenty preterm infants with hematocrit (Hct) < 30% when infant’s age was between 2 to 3 weeks after birth or Hct